ANTIBACTERIAL TEST OF SQUEEZED WATER OF KATUK LEAF ON STREPTOCOCCUS PYOGENES - Novitayanti, Ni Putu S; Rahayu, Titien; Sindrawati, Sindrawati (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Background: Many infectious diseases still can be found in developing countries, including Indonesia. The common type of infection is upper respiratory tract infection (URTI) in which one of the diseases is pharyngitis. About 5% - 40% of pharyngitis cases are caused by Streptococcus pyogenes. One of the treatments for bacterial infection is antibiotics, but the increasing number of antibiotic resistance causes the need to find other alternatives such as herbal plants for the treatment. The community of Bali, particularly in Singaraja, often consume the squeezed water of Katuk leaf (Sauropus androgynus (L.) Merr) to treat pharyngitis.Objectives: This study aims to determine the antibacterial effect of squeezed water of Katuk leaf on Streptococcus pyogenes by measuring the value of the minimum inhibitory concentration (MIC) and the value of the minimum bactericidal concentration (MBC).Methods: The squeezed water of Katuk leaf was obtained through the squeezing method. The antibacterial activity test used the microdilution method of 96 well plates, then the absorbance value was read using a spectrophotometer to determine the MIC value, and streaking was performed to the blood agar strengthened by the results of the spectrophotometric readings to determine the value of MBC.Results: The results showed that the 300 grams of squeezed water of Katuk leaf had MIC values at a concentration of 10% and MBC values at a concentration of 20%.Conclusion: It can be concluded that the squeezed water of Katuk leaf has an antibacterial effect on Streptococcus pyogenes.Keywords: Antibacterial, Sauropus androgynus (L.) Merr, Streptococcus pyogenes